Identification and Characterization of the Chitin Synthase Genes From the Fish Pathogen Saprolegnia parasitica - Rzeszutek, Elzbieta; Díaz-Moreno, Sara M.; Bulone, Vincent (Frontiers in Microbiology, 2019)
Saprolegnia parasitica is a pathogenic oomycete responsible for severe fish infections. Despite its low abundance in the cell wall of S. parasitica, chitin is vital for hyphal growth as the inhibition of its biosynthesis leads to cell death. Here we identified and characterized chitin synthases from S. parasitica as potential targets for anti-oomycete drugs. Bioinformatics analyses allowed the identification of six different putative chitin synthase genes in the genome of the pathogen. The total number of genes was confirmed by Southern blot analysis and their expression levels were determined by quantitative PCR. Four of the six chitin synthase genes were expressed in the mycelium, while the two others exhibited undetectable levels of expression. The mycelium was highly sensitive to the addition of nikkomycin Z (NZ) in the culture medium, which led to a decreased amount of chitin in the cell wall by up to 40% in the conditions tested, and to the formation of abnormal branching structures in the hyphae. The presence of NZ increased the expression level of one of the genes, Chs3, suggesting that the corresponding product is compensating the disruption of chitin biosynthesis in the hyphae. In addition, the activity of isolated chitin synthases was strongly inhibited by NZ in vitro. Altogether our data indicate the importance of chitin synthases for the vegetative growth of S. parasitica and demonstrate that these enzymes represent promising targets for the control of diseases caused by oomycetes.